Reconstructing a changing landscape of human activities in the Iron Age II at Saruq al-Hadid (Dubai) - Wygnańska, Zuzanna; Bagi, Otto; Rądkowska, Joanna; Zych, Iwona; Rempel, Sidney; Juchniewicz, Karol; Boraik, Mansur (Proceedings of the Seminar for Arabian Studies, 2022)
This paper summarizes the results of the Polish excavations in Area F at Saruq al-Hadid in Dubai (UAE), a well-known Iron Age site in the Rub al-Khali. The site was seasonally occupied by groups engaging in large-scale copper production. Despite the limited extent of the Polish study area, conclusions can be drawn regarding the organization of work, long-term changes in site use, and the spatial distribution of various artefact categories within the Iron Age II levels. Two distinct phases were discerned in this period: an older one with traces of extensive metal production, and a younger one with ‘caches’ of metal objects of economic nature and/or ritual significance but no evidence of metallurgical activity. The first phase included a series of charcoal piles, as well as vast quantities of metallurgical artefacts. The area was seemingly divided into specialized zones, each one displaying a different distribution of artefact categories. The disparity in the spatial distribution between different sectors suggests that mass production coexisted with small-scale manufacturing and/or trade activities. In the following phase, industrial practices were entirely abandoned and at some point, the area changed its character and became primarily a place for hoarding metal artefacts, a practice not recognized in earlier levels.